PENGARUH CURRENT RATIO (CR) DAN DEBT TO EQUITY RATIO (DER) TERHADAP HARGA SAHAM PADA PT. INDOFOOD SUKSES MAKMUR TBK. PERIODE 2014-2023 - Isneini Zahra, Mudrika; Intan Sari, Widya (Journal of Research and Publication Innovation, 2024)
This study aims to determine the influence of Current Ratio and Debt to Equity Ratio on Stock Price partially and simultaneously in PT. Indofood Sukses Makmur Tbk. (INDF) in 2014-2023. This research method is a quantitative method. The population used in this study is the entire financial statements of PT. Indofood Sukses Makmur Tbk. in 2014-2023 and the sample in this study is the company's financial statements in the form of balance sheets and income statements of PT. Indofood Sukses Makmur Tbk. in 2014-2023. The data analysis techniques used are descriptive analysis, classical assumption test, statistical analysis, determination coefficient test and hypothesis testing. The results of this study show that partially the Current Ratio does not have a significant effect on the Stock Price, the results of the t-test calculation are obtained t_hitung is smaller than t_tabel (-1,510 < 2,306) and a significant value of 0.175 > 0.05. Meanwhile the Debt to Equity Ratio partially has a significant effect on the Stock Price, The results of the t-test calculation were obtained t_(hitung )is greater than t_(tabel )(2,840 > 2,306) and significant values of 0.025 < 0.05. The results of the F test research show that the Current Ratio and Debt to Equity Ratio simultaneously affected the Stock Price, the results of the F test calculation were obtained F_hitung is greater than F_(tabel )(6,166 > 4,7) and the significance value was 0.029 < 0.05.